Identification of Microrna-21 as a Pro-Invasive Taget in Urothelial Cell Carninoma - Tan, Keai Sinn (2011)
MiRNAs are short non-coding endogenous RNA molecules that play substantial roles in human development and cell lineage decisions. It has been shown to regulate gene expression by controlling messenger RNA (mRNA) translation efficiency. There are emerging evidences suggesting that miRNA plays a critical role in cancer initiation and progression, acting either as tumor suppressors or oncogenes. This study is aimed at identifying mRNA expression patterns associated with the invasiveness of Urothelial Cell Carcinoma (UCC) cell lines and functional targeting of specific miRNAs that potentially regulate these target genes. Microarray-based global gene expression profiling of EJ28 (invasive) and RT112 (non-invasive) cells was performed to identify differentially regulated genes (P<0.01). Loess normalization using non-differentially expressed genes was performed by a rank invariant selection method to normalize the logarithmic expression ratios. Non-parametric Wilcoxon rank-sum test was used to identify top differentially expressed genes. Gene ontology was assigned to the top dysregulated genes using GeneDecks V3 online software (p<0.01) and the comprehensive set of functional annotation tools of DAVID v6.7. Genes linked to metastasis were identified as amongst the top dysregulated genes, and they were correlated to miR-21 and other miRNAs based on in silico prediction. Several genes such as SERPINB5, TIMP3 and TPM1 were predicted to be potentially regulated by miR-21. Several phenotype assays (matrigel invasion, migration and cell proliferation) were conducted to characterize the phenotypic effects of miR-21 expression modulation. The relative proliferation rate at 144 hours of RT112 cells transfected with miR-21 inhibitor decreased dramatically, at 33.23% and 36.96% as compared to untransfected sample control and mock transfection control, respectively. Consistently, the relative proliferation rate at 96 hours of EJ28 cells transfected with miR-21 inhibitor decreased by 10.20% and 12.13% as compared to untransfected and mock transfected controls, respectively. In the cell migration assay, knockdown of miR-21 in RT112 cells showed a 30.44% decrease in cell migration rate at 27 hours. The migration rate was reduced more significantly in knockdown EJ28 cells (47.38% at 27 hours). RT112 miR-21 knockdown cells demonstrated an invasion potential decrease of 3.41 and 3.29 fold as compared to untransfected and mock transfection controls, respectively. As for EJ28 cells, the invasion potential decreased by 2.53 and 2.33 fold as compared to untransfected and mock transfection controls, respectively. Silencing of miR-21 in both non-invasive and invasive bladder cancer cell lines was then demonstrated to have an effect on cell proliferation, migration and invasion. In conclusion, miR-21 is a potential key regulator in UCC progression and invasion, making it a likely biomarker in the future.